Odpowiedzi

2010-01-13T17:26:13+01:00
A) a+(a-b)= a+a-b= 2a-b
b) 2x-(x+4)= 2x-x-4= x-4
c) 7-(-x+6)= 7+x-6= 1+x
d) -(x+4)+(x-5)= -x-4+x-5= -9
e) 1-(t+p)-(t-2)= 1-t-p-t+2= 3-2t-p
f) -(-y+2)+(-2y-4)= y-2-2y-4= -y-6
5 4 5
Najlepsza Odpowiedź!
2010-01-13T17:26:31+01:00
A) a+(a-b)= a+a-b=2a-b
b) 2x-(x+4)= 2x-x-4=x-4
c) 7-(-x+6)= 7+x-6=1+x
d) -(x+4)+(x-5)=-x-4+x+5=1
e) 1-(t+p)-(t-2)= 1-t-p-t+2=3-2t-p
f) -(-y+2)+(-2y-4)= y-2-2y-4=-y-6
8 4 8
2010-01-13T17:26:56+01:00
A) 2a - b
b) x - 4
c) x + 1
d) -9
e) 3 - 2t - p
f) (-y) - 6
2 5 2